PENGARUH BERMAIN TERHADAP KEMAMPUAN SOSIALISASI ANAK SELAMA MENJALANI PERAWATAN DI RSUP DR. SARDJITO - Dewi Listyorini; Endang Zulaicha (Jurnal Berita Ilmu Keperawatan, 2009)
Background. Children is a play period. A healthy child spends most time for active playing and gets more satisfaction than a sick. A sick child looses her play time, friends, and comfortable environment. He has to move to hospital that seems strange for him. That strangeness causes bad experience that influences for his social attitude in the future. Playing gives a chance for kids to express their feelings as long as they are sick. It also supports their growth normally. Objective. This aim research is for knowing the influence of playing to children social ability when they have a treatment before and after being done a playing activity. Method. This research is included in kuantitatif analytical research by one group design, pre and post test design. This research is done from December 2005 until Februari 2006. Samples are taken using accidental sampling technique. The subject is children in 2-6 years old who are opnamed in surgeon room at Dr. Sardjito Hospital. The number of subject is 23 childrens. It is used part test t analitycal technic The accumulation of the data is done before and after the children play a game. Result. Base on analitycal report, it is gotten signification score 0,011(p